Mortality in vegetarians and non-vegetarians: a collaborative analysis of 8300 deaths among 76,000 men and women in five prospective studies. - Key, T; Fraser, G; Thorogood, M; Appleby, P; Beral, V; Reeves, G; Burr, M; Chang-Claude, J; Frentzel-Beyme, R; Kuzma, J; Mann, J; McPherson, K (1998)
OBJECTIVE: To compare the mortality rates of vegetarians and non-vegetarians. DESIGN: Collaborative analysis using original data from five prospective studies. Death rate ratios for vegetarians compared to non-vegetarians were calculated for ischaemic heart disease, cerebrovascular disease, cancers of the stomach, large bowel, lung, breast and prostate, and for all causes of death. All results were adjusted for age, sex and smoking. A random effects model was used to calculate pooled estimates of effect for all studies combined. SETTING: USA, UK and Germany. SUBJECTS: 76,172 men and women aged 16-89 years at recruitment. Vegetarians were those who did not eat any meat or fish (n = 27,808). Non-vegetarians were from a similar background to the vegetarians within each study. RESULTS: After a mean of 10.6 years of follow-up there were 8330 deaths before the age of 90 years, including 2264 deaths from ischaemic heart disease. In comparison with non-vegetarians, vegetarians had a 24% reduction in mortality from ischaemic heart disease (death rate ratio 0.76, 95% CI 0.62-0.94). The reduction in mortality among vegetarians varied significantly with age at death: rate ratios for vegetarians compared to non-vegetarians were 0.55 (95% CI 0.35-0.85), 0.69 (95% CI 0.53-0.90) and 0.92 (95% CI 0.73-1.16) for deaths from ischaemic heart disease at ages <65, 65-79 and 80-89 years, respectively. When the non-vegetarians were divided into regular meat eaters (who ate meat at least once a week) and semi-vegetarians (who ate fish only or ate meat less than once a week), the ischaemic heart disease death rate ratios compared to regular meat eaters were 0.78 (95% CI 0.68-0.89) in semi-vegetarians and 0.66 (95% CI 0.53-0.83) in vegetarians (test for trend P< 0.001). There were no significant differences between vegetarians and non-vegetarians in mortality from the other causes of death examined. CONCLUSION: Vegetarians have a lower risk of dying from ischaemic heart disease than non-vegetarians.